A Fatigue Measuring Protocol for Wireless Body Area Sensor Networks. - Akram, Sana; Javaid, Nadeem; Ahmad, Ashfaq; Khan, Zahoor; Imran, Muhammad; Guizani, Mohsen; Hayat, Amir; Ilahi, Manzoor (Journal of Medical Systems, 2015)
As players and soldiers preform strenuous exercises and do difficult and tiring duties, they are usually the common victims of muscular fatigue. Keeping this in mind, we propose FAtigue MEasurement (FAME) protocol for soccer players and soldiers using in-vivo sensors for Wireless Body Area Sensor Networks (WBASNs). In FAME, we introduce a composite parameter for fatigue measurement by setting a threshold level for each sensor. Whenever, any sensed data exceeds its threshold level, the players or soldiers are declared to be in a state of fatigue. Moreover, we use a vibration pad for the relaxation of fatigued muscles, and then utilize the vibrational energy by means of vibration detection circuit to recharge the in-vivo sensors. The induction circuit achieves about 68 % link efficiency. Simulation results show better performance of the proposed FAME protocol, in the chosen scenarios, as compared to an existing Wireless Soccer Team Monitoring (WSTM) protocol in terms of the selected metrics.